New Insight into the Interfacial Enhancement of Polypropylene Glass Fiber Composites via a Compatibilizer: The Role of Injection Screw Temperature. Issue 2 (1st February 2016) - Li, Yijun; Lin, Yang; Nie, Min; Wang, Qi; Zhang, Xiaofei
ABSTRACT: Polypropylene (PP)glass fiber (GF) composites modified by maleic anhydride-grafted polypropylene (MAH-g-PP) were prepared and the thermal influence on the interfacial properties was characterized and discussed. The results showed that the migration of MAH-g-PP from the PP matrix onto the GF surface was a thermally activated process. To be more specific, with the increasing processing temperature, more MAH-g-PP migrated onto the interface region to bridge PP matrix and GF together and promote the interfacial interaction, resulting in more efficient applied load transfer to GF through the interface. Accordingly, the mechanical properties of PPGF composites were improved with increasing processing temperature. Moreover, based on the content of MAH-g-PP on the surface of the GF and the mobility of MAH-g-PP in the PPGF composites, a temperature-dependent mechanism for the enhanced interface was proposed. We suggest this study not only provides a guide to adjust processing parameters to prepare high-performance PPGF composite, but also would be applicable for other immiscible systems.